FRI0620 Low educational attainment is associated with poor patient status at the initial visit of patients with rheumatoid arthritis (RA) or osteoarthritis (OA) at the initial visit to a rheumatology setting, with similar patterns in patients with either diagnosis. (12th June 2018) - Schmukler, J.; Castrejon, I.; Pincus, T.; Block, J.
Abstract : Background: Low educational attainment is associated with a higher prevalence, morbidity, and mortality of many diseases, including rheumatoid arthritis (RA) (J Chronic Dis 1985; 38:973–84) and osteoarthritis (OA) (J Clin Epidemiol 1992;45:139–47). These associations often are attributed to limited access of disadvantaged people to medical services (Ann Intern Med 1998;129:412–6), although some have suggested that these differences are explained primarily by differences in patient self-management (Ann Intern Med 1998;129:406–11). Objectives: To study clinical status of patients with RA or OA, all of whom had access to rheumatology care, at their initial visit. Methods: All patients with all diagnoses seen at an academic rheumatology site complete a self-report multidimensional health assessment questionnaire (MDHAQ) at each visit. MDHAQ includes 3 0–10 scales for physical function (FN), pain (PN) and global assessment (PATGL), compiled into a 0–30 routine assessment of patient index data (RAPID3). Patient-reported FN, PN, PATGL and RAPID3 were compared in new patients with a primary diagnosis of either RA (n=66) or OA (n=66) at a first visit in 3 groups according to years of formal education, <12, 12, and >12 years, using analysis of variance (ANOVA). Results: Mean MDHAQ scores were quite similar in OA vs RA, and varied similarly according to education level (table 1). In all patients, mean RAPID3 was 15.4 in OA vs 15.3 in RA; in those with <12 years, 18.2 in OA vs 19.8 in RA; in those with 12 years, 15.9 in OA vs 16.0 in RA; in those with >12 years, 14.0 in OA vs 13.7 in RA (p=0.11 for OA, p=0.04 for RA) (table 1). FN scores were 3.9 in both groups with <12, 3.3 in both groups with 12, and 2.3 in OA vs 2.4 in RA patients with>12 years of education (p=0.02 for OA, p=0.08 for RA). PN scores were 7.3 and 8.5 for OA vs RA with <12 years, 7.1 and 6.2 for OA vs RA with 12 years, and 6.7 vs 5.9 for OA vs RA patients with >12 years of education (p=0.69 for OA, p=0.02 for RA). PATGL was 7.0 vs 7.4 for OA vs RA with <12 years, 5.5 and 6.5 for OA vs RA with 12 years, and 5.1 and 5.4 in OA vs RA patients with >12 years of education (p=0.14 for OA, p=0.12 for RA). Conclusions: Low education was associated with RAPID3 and all component scores similarly in RA and OA. Differences according to formal education level were greater than by diagnosis, which were negligible. These variations do not appear attributable to differences in access to medical services. Disclosure of Interest: J. Schmukler: None declared, I. Castrejon: None declared, T. Pincus Shareholder of: Dr. Pincus holds a copyright and trademark on MDHAQ and RAPID3 for which he receives royalties and license fees. All revenue is used to support further development of quantitative questionnaire measures for patients and doctors in clinical rheumatology care., J. Block: None declared